Tantangan Penegakan Hukum Persaingan Usaha Pada Industri Perbankan Syariah - Huta Disyon; Fildzah Rio (Komisi Pengawas Persaingan Usaha, 2022)
Islamic Banking Law obliged business actors to take certain actions in order to create a stronger sharia banking industry. For example, the obligation to separate the Sharia Business Unit from the conventional parent bank and the minimum core capital requirement. To implement these regulations, Islamic banks may engage in several corporate actions, including spin-offs, mergers, and takeovers of business units. This research is intended to examine the potential violations of Law 5/1999 in the implementation of those Islamic bank corporate actions. The research method used is normative juridical, by reviewing Islamic Banking Law and Law 5/1999. According to the research, it has been determined a significant number of corporate actions in the Islamic banking sector would occur in 2023, necessitating increased attention from the KPPU, BI, and OJK to supervise these corporate actions in order to ensure healthy competition in the Islamic banking sector.